Integrating the Nationally Determined Contributions (NDCs) and National Biodiversity Strategies and Action Plans (NBSAPs) through the Water, Energy, Food and Ecosystems (WEFE) nexus approach - Mabhaudhi, Tafadzwanashe; Elias, Marlene (2024)
As the UN Biodiversity Conference closes and the UN Climate Change Conference begins, this blog describes a new brief that calls for integrating and harmonizing policy frameworks to combat climate change and biodiversity loss through water-energy-food-ecosystems (WEFE) nexus approaches.